If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5/9x-1+2/3x=5
We move all terms to the left:
5/9x-1+2/3x-(5)=0
Domain of the equation: 9x!=0
x!=0/9
x!=0
x∈R
Domain of the equation: 3x!=0We add all the numbers together, and all the variables
x!=0/3
x!=0
x∈R
5/9x+2/3x-6=0
We calculate fractions
15x/27x^2+18x/27x^2-6=0
We multiply all the terms by the denominator
15x+18x-6*27x^2=0
We add all the numbers together, and all the variables
33x-6*27x^2=0
Wy multiply elements
-162x^2+33x=0
a = -162; b = 33; c = 0;
Δ = b2-4ac
Δ = 332-4·(-162)·0
Δ = 1089
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1089}=33$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(33)-33}{2*-162}=\frac{-66}{-324} =11/54 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(33)+33}{2*-162}=\frac{0}{-324} =0 $
| 3/7+y=19/14 | | 4s+6=7s | | 2x-10-8x=14 | | 9x-4=81^2x-3 | | 13=5v+6/8+4v-3/4 | | -12+11x-12x=21 | | 2j=3j-7 | | A=(3x-4)-(-2x+5) | | F=6+12t | | 12x-11=5x+3 | | -6x-42+12x=90 | | 596-7x)+5(x-12)=0 | | -6+4r=6r | | x9-1=-10 | | 2h-7=12h-2h+3 | | 5(2x+9)=-17+52 | | 2,5x^2+4x=0 | | -3z=-4z+9 | | 1/8x+6=34 | | 5/3x+1/3x=222/3+6/3x | | G(x)=32/5x+55 | | 5/x=40/6= | | 42/g=6 | | 6(9x−10)+2(18−3x)=−8 | | -12+4m=-2-6(-4+m) | | 3^2-a=30 | | 9-8b=2 | | 0.5x-3=7.5 | | 7x-18+x=6 | | 6h-9=-9 | | 6+3b=14 | | 14d+20=20 |